Debt sustainability and economic convergence of euro-area Member States: Challenges and Solutions - Paolo Manasse (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
This paper argues that fiscal convergence in the Euro area has been achieved at the expenses of real divergence in unemployment, investment and at, at least temporarily, growth. Statistical and econometric analysis support the view that the current fiscal framework has addressed debt sustainability concerns, but has imparted a pro-cyclical bias, which has contributed to economic divergence. The recent flexibility guidelines are a step in the right direction, but they are unlikely to have sizable effects. A reform of the fiscal framework and a mechanism for an intra-European unemployment insurance scheme is proposed.
Keywords: E02; E61; E62; H6; 330